Environmental Factors Affecting Human Health 2020
DOI: 10.5772/intechopen.90661
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Industry Wastes as Wealth of Organic Carbon for Soil

Abstract: The organic carbon management in the soil and its relationship with soil physiochemical and biological characteristics to increase the crop productivity have been described based on the byproducts of sugarcane. In this chapter, the available information on the nutrient content especially the organic carbon of various by-products of sugarcane, paves the way for incorporation of waste materials and its compost for improving the soil fertility by soil scientists and agronomists, and further, the ecologists will r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Moreover, it also has a slightly alkaline pH of 8.54. The organic content of pressmud was 17.62%, indicating a significant concentration of macro-and micronutrients [13]. Pressmud contains a variety of macro-and microelements that plants need, frequently combined with other organic fertilizer sources in numerous techniques [3].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it also has a slightly alkaline pH of 8.54. The organic content of pressmud was 17.62%, indicating a significant concentration of macro-and micronutrients [13]. Pressmud contains a variety of macro-and microelements that plants need, frequently combined with other organic fertilizer sources in numerous techniques [3].…”
Section: Resultsmentioning
confidence: 99%
“…Total soil organic carbon stocks in Polish upland meadows range from 1.27% to 17.9% in an optimally moist habitat [33]. Considering that organic matter contains 58% organic carbon [34], the percentage of OM in the accumulation layer of the soil cover of a mesic meadow ranges from 2.18% to 30.86%. There was a decrease in OM content from 23.54 to 20.01% in soil S3 and 25.34% to 20.48% in S5.…”
Section: Discussionmentioning
confidence: 99%
“…Such soil conditions are known to adversely affect the physiological (reduced photosynthetic and photochemical efficiency, stomatal limitation and/or metabolic impairment) and agronomic efficiency of growing plants (Hajiboland, Norouzi, & Poschenrieder, 2014; Munns, 2002; Tavakkoli, Fatehi, Coventry, Rengasamy, & McDonald, 2011). In addition, PM is known to increase soil organic carbon (SOC) and nutrient availability (Krishnaveni, Chinnasamy, Elumalai, & Muthaiyan, 2020), improve soil physical conditions (soil's water‐holding capacity, clay flocculation and aggregate stability) (Bhosale, Chonde, Nakade, & Raut, 2012; James, 2020; Lwin, Seo, Kim, Owens, & Kim, 2018) that, in turn, help improve soil water movement and facilitate the leaching of Na + ions to deeper soil layers (Choudhary, 2017; Qadir, Schubert, Ghafoor, & Murtaza, 2001), thus improving plant growth, crop biomass and yield. The results of this study thus confirm earlier studies that have observed beneficial effects of pressmud application in improving the plant salt tolerance, their associated improvement in environmental adaptability and the final crop harvest under sodic conditions (Dotaniya et al, 2016; A. Kumar et al, 2017; Sheoran et al, 2021; Yaduvanshi & Swarup, 2005).…”
Section: Discussionmentioning
confidence: 99%